A comparison of the utility of different step-indices to translate the physical activity recommendation in adolescents. - Mayorga-Vega, Daniel; Casado-Robles, Carolina; López-Fernández, Iván; Viciana-Ramírez, Jesus (Taylor & Francis, 2020)
Previous studies translating the daily moderate-to-vigorous physical activity (MVPA) recommendation of total steps/day among adolescents are inconsistent, and those with cadence-based steps are scarce. The main purpose was to compare the accuracy of different daily steps index-based cut-points related to the daily 60 minutes of MVPA recommendation measured by a waist-worn accelerometer for adolescents. Following a cross-sectional design, 428 Spanish adolescents (final sample 351, 50.4% males), aged 13−16 years old, wore an ActiGraph GT3X/+ accelerometer (reference standard = MVPA; index tests = total steps/day, average steps/min and peak 1-min cadence) on the right hip for eight consecutive days. 32.5% of the adolescents met the daily MVPA recommendation. The multiple ROC curve comparisons showed that the accuracy of the daily total step-based recommendation (AUC = 0.97) was statistically higher than for those with the steps/min (AUC = 0.90) and peak 1-min cadence (AUC = 0.58) (p < 0.001). The 10,000-step-per-day cut-point (k= 0.59−0.83) showed highest accuracy values than the 12,000 steps/day (k= 0.20−0.32). Daily total step-based recommendations are more accurate than those with steps/min and peak 1-min cadence for classifying adolescents as being physically active or inactive. A 10,000-step-per-day target is simple and accurate for both male and female adolescents.
Keywords: Ejercicio físico; Adolescentes; Activity trackers; Steps per day; Step counts; Walking cadence; Thresholds; Youth